2018
DOI: 10.5121/ijcnc.2018.10205
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Blowfish Algorithm on Supercomputer IMAN1

Abstract: Cryptographic applications are becoming increasingly more important in today's world of data exchange, big volumes of data need to be transferred safely from one location to another at high speed. In this paper, the parallel implementation of blowfish cryptography algorithm is evaluated and compared in terms of running time, speed up and parallel efficiency. The parallel implementation of blowfish is implemented using message passing interface (MPI) library, and the results have been conducted using IMAN1 Supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The IDEA implementation based on portioning data where every processor executes the same code with the same key for all concurrently on data portion which allocated to it. Parallel IDEA evaluated by multiple input sizes (0.09, 0.19, 0.39,0.78, 1.56,3.12, 6.25,12.5, 25,50 MByte) and different numbers of processors (1,2,3,4,8,16,32,64,128).…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The IDEA implementation based on portioning data where every processor executes the same code with the same key for all concurrently on data portion which allocated to it. Parallel IDEA evaluated by multiple input sizes (0.09, 0.19, 0.39,0.78, 1.56,3.12, 6.25,12.5, 25,50 MByte) and different numbers of processors (1,2,3,4,8,16,32,64,128).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…In [16], the authors showed the performance evaluation of the blowfish algorithm in the parallel platform, the algorithm is implemented using the MPI library, and the experiment is performed on an IMAN1 supercomputer. The experimental results showed that the parallel algorithm achieved the best value when the number of processors is 32 for a plaintext size of 160 Mbyte.…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…1) Conventional digital forensics cannot be used to investigate the incident in cloud computing on the basis of various factors such as the distributed nature of cloud computing [64] [65], large resources rather than limited resources in local devices, a large number of data centers located in multiple locations, the presence of third parties and many other factors.…”
Section:  Cloud Computing Forensicsmentioning
confidence: 99%